Acute kidney injury after coronary artery bypass graft surgery: a narrative review of causes, diagnosis, and prevention - Jannati, Mansour; Kojuri, Javad (Family Medicine & Primary Care Review, 2021)
Acute kidney injury (AKI) after coronary artery bypass grafting (CABG) is a common cardiac event associated with short and long-term consequences and occurs in 30–51% of CABG patients. AKI may be associated with many other factors and is also responsible for many other pathologies. An increased level of serum creatinine (SCr) after surgery is one of the signs of AKI that may occur more often during cardiopulmonary bypass (CPB) in susceptible individuals. Preparing preoperative checklists is a good practice for the prevention of AKI. Defining new opportunities and strategies of perioperative care is a useful procedure for decreasing the risk of AKI after cardiac surgery. Collecting more data on preoperative risk factors and improving the intraoperative practices may decrease the incidence of AKI in the aggregate population. In this review study, we are going to review the literature on the pathophysiology of AKI and introduce the discussion about the features of patients who are more at the risk of AKI than others.